2024
DOI: 10.3389/fmicb.2024.1348729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary D-lactate levels on rumen fermentation, microflora and metabolomics of beef cattle

Qian Gao,
Jianfu He,
Jin Wang
et al.

Abstract: IntroductionExcessive intake of lactate caused by improper use of silage in animal husbandry has adverse effects on rumen fermentation, such as rumen acidosis. The speed of absorption and metabolism of D-lactate in rumen epithelial cells was slower than that of L-lactate, making D-lactate more prone to accumulate and induce rumen acidosis. Therefore, this study was conducted to explore the effects of dietary D-lactate levels on rumen fermentation of beef cattle and its mechanism in an in vitro system.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…In this study, at the phylum level, we observed Bacteroidota , Proteobacteria, and Firmicutes as communities with relatively high abundance. At the genus level, Prevotella , Succinivibrionaceae UCG-002, and Rikenellaceae RC9_gut group were communities with relatively high abundance, which is consistent with the dominant communities in rumen fluid in our previous study [ 30 ]. This indicates that our bovine rumen fluid fistula and RUSITEC system have good stability, and the data obtained can also be reproduced well in real animal experiments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, at the phylum level, we observed Bacteroidota , Proteobacteria, and Firmicutes as communities with relatively high abundance. At the genus level, Prevotella , Succinivibrionaceae UCG-002, and Rikenellaceae RC9_gut group were communities with relatively high abundance, which is consistent with the dominant communities in rumen fluid in our previous study [ 30 ]. This indicates that our bovine rumen fluid fistula and RUSITEC system have good stability, and the data obtained can also be reproduced well in real animal experiments.…”
Section: Discussionsupporting
confidence: 89%
“…Microbiological analysis of fermentation broth samples was conducted by Beijing Ovison Gene Technology Co., Ltd. (Beijing, China). The detailed purification, quantification, sequencing steps and analytical methods are consistent with those in our previous studies [ 30 ], as described in detail below.…”
Section: Methodsmentioning
confidence: 60%